Design and simulation of a low-power 0.18 Î¼m CMOS MedRadio band LNA - Mubin, M.A. (IEEE Computer Society, 2018)
This paper presents the design and simulation of a low-power MedRadio band low noise amplifier (LNA) using standard 0.18 Î¼m CMOS process. This LNA utilizes current reuse and active shunt feedback circuit techniques to achieve (on simulation) very low power operation with gain of more than 18 dB, noise figure of less than 5 dB, and input return loss of more than 10 dB between 401 MHz to 406 MHz MedRadio band. Total power consumption of this LNA is just under 0.6 mW where approximately 0.1 mW is due to the active shunt feedback network. The design and simulation were done in Cadence IC5 with Silterra's 0.18 Î¼m CMOS technology. Â© 2017 IEEE.